DELIVERING CUSTOMER SERVICE EXCELLENT FOR SUSTAINABLE HOSPITALITY BUSINESS (CASE STUDY AT TRANS RESORT BALI) - Augustinus, Daniel Cassa; Gordon, Tiffany (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Because it fosters repeat business, positive word-of-mouth advertising, and a steady clientele, customer loyalty is essential to a hotel’s success. The goal of the study is to determine how customer loyalty at Trans Resort Bali is impacted by service recovery, complaint handling, and perceived value. Because it fosters repeat business, positive word-of-mouth advertising, and a steady clientele, customer loyalty is essential to a hotel’s success. The goal of the study is to determine how customer loyalty at Trans Resort Bali is impacted by service recovery, complaint handling, and perceived value. Customer loyalty at The Trans Resort Bali is significantly impacted by the research’s findings about service recovery. Customer loyalty at The Trans Resort Bali is significantly impacted by how complaints are handled. Customer loyalty is significantly impacted by perceived value at The Trans Resort Bali. At The Trans Resort Bali, factors including perceived value, complaint resolution, and service recovery have a big impact on client loyalty. In order to guarantee a satisfying and unforgettable stay, the hotel should implement a proactive and sympathetic service recovery approach by quickly responding to guest complaints, extending heartfelt apologies, and offering practical solutions. The hotel can improve how it handles complaints by creating a more efficient communication system, giving employees the freedom to handle problems quickly, and regularly asking for input to identify and remedy areas where customers are not satisfied.